Built in Potential of a-Si:H Based p-i-n Solar Cell at Different Energy Gap of Intrinsic Layer - Yuniarsih, Rahayu Setyo; Purwandari, Endhah; Misto, Misto; Supriyanto, Edi; Supriyadi, Supriyadi (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2018)
The photovoltaic process inside a solar cell can be described using the distribution of electrostatic potential in the material. In this paper, the magnitude of the electrostatic potential of the solar cell for the p-i-n junction type is analyzed as the built in potential due to the diffusion activity of electrons and holes. The magnitude of the electrostatic potential is obtained by solving the Poisson and Continuity equations, which are applied to a-Si: H based materials. The difference in built in potential at the p-i and i-n junctions is obtained as a function of the energy gap of the intrinsic layer.